Закономерности формирования параметров теплового процесса при шлифовании - Кленов, Олег Станиславович (НТУ "ХПИ", 2015)
Получены аналитические зависимости для определения температуры резания, глубины проникновения тепла в адиабатический стержень и времени нагрева адиабатических стержней, множеством которых представлен снимаемый припуск при плоском шлифовании. Установлено, что во времени температура резания увеличивается, асимптотически приближаясь к постоянному значению. Глубина проникновения тепла в адиабатический стержень и время нагрева адиабатического стержня также изменяются по закону изменения температуры резания.

Analytical dependence for determining the temperature of the cutting, the depth of penetration of heat in the core and adiabatic heating time adiabatic rods, which presented a variety of removable allowance at flat grinding. It was found that over time, taking into account the processing of traffic along the adiabatic heat source rod at a constant speed, these param eters are increased, asymptotically approaching a certain constant values. At this time, the adiabatic heating rod less time of its contact with the grinding wheel, which involves reducing the temperature in the grinding of cutting as compared with the case where there is no movement of the adiabatic heat source along the rod. The calculation of the heat in the outgoing chip formed in the surface layer of the workpiece. It is found that with increasing temperature up to 1500 °C cutting adiabatic rod requires more heat than the chip formed and the temperature increases from 1500 to cut the maximum value - 2000 °C, conversely, more heat is generated in the chips out.
Laws of formation of thermal process parameters for grinding
Keywords: резание; температура; стержень адиабатический; глубина шлифования; grinding process; multipass grinding; cutting temperature; thermal process; adiabatic rod; grinding depth